Raise of nanopowders excess energy by electron beams exposure; The 8th International Forum on Strategic Technology (IFOST-2013), June 28 - July 1, 2013, Ulaanbaatar, Mongolia; Vol. 1 - Ilyin A. P. Aleksandr Petrovich (2013, 2013)
Title screen